SVEOBUHVATAN OSVRT NA NOVU HRANU NA BAZI LANA I INDUSTRIJSKU UPOTREBU LANA : OD 2014. GOD. DO DANAS - YAWALE, PRIYA (Food and Feed Research, 2022)
Flaxseed or linseed is an oilseed obtained from a herb known as flax plant. It is a valuable source of various bio-active components such as omega-3 polyunsaturated fatty acids, protein, lignan, dietary fibre and phytochemicals. The in-vivo, in-vitro studies and researches on human subjects conducted throughout the globe on health benefits associated with consumption of various forms of flaxseed are discussed in detail in this review. It provides an insight on recent developments and potential applications on employability of flaxseeds in whole, powdered, oil or flour form in an array food products and industrial applications. The details pertaining to novel health benefits associated with the flaxseed and information related to commercially available flaxseed based/ enriched product is also the salient feature of the review. Here, we have provided state of the art recent comprehensive information post the first detailed review published pertaining to flaxseed as a modern food in 2014.